Pebbles on the beach - Raynham, Alex (Dominoes Quick starter, 2012)
Abby is a teenager, and doesn't talk much to her parents. Abby's dad works hard for an oil company, and Abby's mom doesn't like her freinds. Then, one summer, Abby stays with her crazy Aunt May in California. Here, with Aunt May ahd her young neighbours Diego and Bianca, she learns to see things differently. But, one night, there's an oil spill on the beautiful beach near their home. What can Abby, her aunt, and the neighbours do? And who answers Abby's call for more help? And how?